Retrofit strategies to improve energy efficiency through the integration of thermal insulation into the residential buildings of Saudi Arabia - Hassan Hassan Umar; Omar S. Asfour (Case Studies in Thermal Engineering)
Approximately 70 % of residential buildings in Saudi Arabia lack adequate thermal insulation, resulting in high cooling demands that contribute to more than 47 % of the nation's electricity consumption. This study aimed to evaluate several thermal insulation retrofit strategies for typical residential buildings in Saudi Arabia. A mixed-methods approach was employed through a combination of expert interviews and energy simulations conducted using DesignBuilder software. A total of 24 retrofit scenarios, comprising different combinations of internal and external walls, roof insulation, window glazing enhancements, and HVAC system upgrades, were assessed. A multi-criteria decision analysis (MCDA) using the TOPSIS method was applied to rank scenarios based on three key indicators: energy savings, payback periods, and material lifespan. Energy savings across the scenarios ranged from 12 % to 75 %. The most effective scenario, which combined external roof insulation with an HVAC upgrade, achieved 65.5 % energy savings with a payback period of 8.6 years and a closeness-to-ideal score (Ci) of 0.92. Key barriers identified by experts included high material costs, limited skilled labor, regulatory constraints, and supply chain delays. These findings provide targeted guidance in selecting optimal retrofit strategies to enhance the energy performance of residential buildings in hot climates.